Mucosal Nanoemulsion Allergy Vaccine Suppresses Alarmin Expression and Induces Bystander Suppression of Reactivity to Multiple Food Allergens - Farazuddin, Mohammad; Landers, Jeffrey J.; Janczak, Katarzyna W.; Lindsey, Hayley K.; Finkelman, Fred D.; Baker, James R.; O’Konek, Jessica J. (Frontiers in Immunology, 2021)
We have demonstrated that intranasal immunotherapy with allergens formulated in a nanoemulsion (NE) mucosal adjuvant suppresses Th2/IgE-mediated allergic responses and protects from allergen challenge in murine food allergy models. Protection conferred by this therapy is associated with strong suppression of allergen specific Th2 cellular immunity and increased Th1 cytokines. Here we extend these studies to examine the effect of NE-allergen immunization in mice sensitized to multiple foods. Mice were sensitized to both egg and peanut and then received NE vaccine formulated with either one or both of these allergens. The animals were then subjected to oral challenges with either egg or peanut to assess reactivity. Immunization with NE formulations containing both egg and peanut markedly reduced reactivity after oral allergen challenge with either allergen. Interestingly, mice that received the vaccine containing only peanut also had reduced reactivity to challenge with egg. Protection from oral allergen challenge was achieved despite the persistence of allergen-specific IgE and was associated with strong suppression of both Th2-polarized immune responses, alarmins and type 2 innate lymphoid cells (ILC2). NE-induced bystander suppression of reactivity required IFN-γ and the presence of an allergen in the NE vaccine. These results demonstrate that anaphylactic reactions to food allergens can be suppressed using allergen-specific immunotherapy without having to eliminate allergen-specific IgE and suggests that modulation of Th2 immunity towards one allergen may induce bystander effects that suppress reactivity to other allergens through the induction of IFN-γ and suppression of alarmins in the intestine. In addition, these data suggest that a NE vaccine for a single food allergen may lead to a global suppression of allergic responses to multiple foods.